Student Perceptions of Humanist Literacy - Sasmita Chairuna; Uli Ramadani Siagian; Sulaiman Horta Siregar; Muhammad Asri; Muhammad Shaleh Assingkily (Yayasan Zia Salsabila, 2024)
Literacy ability can empower and improve individual quality because of its